Encyclopedia of the Harlem Renaissance - Wintz, Cary D., 1943-; Finkelman, Paul, 1949- (Routledge, 2004)
An interdisciplinary look at the Harlem Renaissance, it includes essays on the principal participants, those who defined the political, intellectual and cultural milieu in which the Renaissance existed; on important events and places.
Keywords: African American arts -- New York (State) -- New York -- History -- 20th century -- Encyclopedias.; Harlem Renaissance -- Encyclopedias.; Arts noirs américains -- New York (État) -- New York -- Histoire -- 20e siècle -- Encyclopédies.; Harlem Renaissance -- Encyclopédies.; ART -- Reference.; ART -- Performance.; SOCIAL SCIENCE -- Ethnic Studies -- African-American Studies.; REFERENCE -- Encyclopedias.; HISTORY -- United States -- 20th Century.; African American arts; Harlem Renaissance; New York (State) -- New York; 1900-1999; Electronic books.; Encyclopedia; encyclopedias.; Encyclopedias; History; Encyclopedias.; Encyclopédies.